Celine [large type] : a novel - Heller, Peter, 1959- (Center Point Large Print, 2017)
A luminous, spine-tingling novel of suspense--the story of Celine, an elegant, aristocratic private eye who specializes in reuniting families, trying to make amends for a loss in her own past.